Anti-lipolytic activity and phytochemical screening of Chelianthesalbomarginata against pathogenic microorganisms - Jarial, Rini; Singh, Lakhveer; Zularisam, A. W.; Kanwar, S. S. (IIUM, Malaysia, 2017)
The aim of the present study was to evaluate the therapeutic properties of selected fern, Chelianthusalbomarginata and to identify its functional compounds. The methanolic fern-extract (MFE) of these ferns was assessed for anti-bacterial activities by measuring inhibition zones against a panel of pathogenic bacterial strains using agar diffusion method. MFE at a concentration of 25 Î¼g/ml showed marked anti-bacterial activity against all bacterial strains (6-23mm zone of inhibition) and was maximum against Enterobacter sp (23 mm). In addition, the MFE of C. albomarginata had the best MIC values of 2.25Âµg/ml against S. aureus and Enterobacter sp., respectively. The MFE also possessed good anti-lipolytic activity (66.5%) against a porcine pancreatic lipase (PPL) and cholesterol oxidase inhibition (79%). This result showed that MFE of C. albomarginata under optimal concentration is not only a potent source of natural anti-oxidants and anti-bacterial activity but also possesses efficient cholesterol degradation and anti-lipolytic activities, that is to be beneficial in the body weight management.